The noble gases as geochemical tracers - Burnard, Peter; Burnard, Pete (Springer, 2013)
The twelve chapters of this volume aim to provide a complete manual for using noble gases in terrestrial geochemistry, covering applications which range from high temperature processes deep in the Earth's interior to tracing climatic variations using noble gases trapped in ice cores, groundwaters and modern sediments. Other chapters cover noble gases in crustal (aqueous, CO2 and hydrocarbon) fluids and laboratory techniques for determining noble gas solubilities and diffusivities under geologically relevant conditions. Each chapter deals with the fundamentals of the analysis and interpretation of the data, detailing sampling and sampling strategies, techniques for analysis, sources of error and their estimation, including data treatment and data interpretation using recent case studies.--
Keywords: Aufsatzsammlung; Methode; Isotopengeologie; Isotopengeochemie; Isotop; Edelgas; Untersuchungsmethode; Edelgasisotop; Geochemie; Tracer; Geochemische Analyse; Geowissenschaften